Anti-α-glucosidase and antiglycation activities of galls from Guiera senegalensis J.F. Gmel (combretaceae) - Pierre Alexandre Eric Djifaby SOMBIE; Rahman M HAFIZUR; Moussa COMPAORÉ; Martin KIENDREBEOGO; Muhammad Iqbal CHOUDHARY; Odile Germaine NACOULMA (International Journal of Phytomedicine, 2018)
The hypoglycemic activity of Guiera senegalensis used in Burkinabe folk medicine has been already reported. The aim of this study was to investigate the in vitro antidiabetic activity from galls of G.senegalensis. The extracts and methanol fractions from galls of G. senegalensis showed strong α-glucosidase inhibitory activity compared with acarbose. The ethyl acetate fraction from methanol extract (EA/ME) showed potent antiglycation activity in an in vitro assay system. The galls did not show inhibition activity against α-chymotrypsin. The α-glucosidase inhibitory activity along with its antiglycation activity may open a new perspective for the use of G. senegalensis for the diabetic subject. The data suggests that consumption of G senegalensis galls as an infusion or in food and pharmaceutical preparations may be useful for the management of diabetes and its complications.